Comparison of timolol 0.5% + brimonidine 0.2% + dorzolamide 2% versus timolol 0.5% + brimonidine 0.2% in a Mexican population with primary open-angle glaucoma or ocular hypertension - Baiza-Durán LM (Dove Medical Press, 2012)
Leopoldo Martín Baiza-Durán, Juan Francisco Llamas-Moreno, Clotilde Ayala-BarajasClinical Research Department, Laboratorios Sophia, SA de CV Guadalajara, Jalisco, MéxicoBackground: The purpose of this study was to evaluate the efficacy and safety of two fixed combinations, ie, timolol 0.5% + brimonidine 0.2% + dorzolamide 2% (TBD) versus timolol 0.5% + brimonidine 0.2% (TB) in patients with primary open-angle glaucoma or ocular hypertension.Methods: We performed a 3-month, randomized, double-blind study in patients with primary open-angle glaucoma or ocular hypertension and an intraocular pressure of 21–30 mmHg. Patients were randomly assigned to receive one drop of TBD or TB twice a day. The primary efficacy endpoint was change in intraocular pressure after 3 months of treatment. Safety measures were assessed by the presence of adverse events.Results: Mean baseline intraocular pressure was similar at 8 am and 4 pm in the treatment groups (TBD 22.3 ± 0.9 mmHg, TB 22.4 ± 1.8 mmHg, P = 0.558; TBD 19.02 ± 1.3, TB 19.08 ± 1.2, P = 0.536, respectively). At the end of the study, the mean intraocular pressure was significantly lower in the TBD group at both 8 am (16.19 ± 2.0 mmHg versus 18.35 ± 1.4 mmHg, P = 0.000) and 4 pm (14.74 ± 2.4 mmHg versus 16.77 ± 1.4 mmHg, P = 0.000).Conclusion: Fixed-combination TBD was more effective than fixed-combination TB for reducing IOP in patients with primary open-angle glaucoma.Keywords: primary open-angle glaucoma, ocular hypertension, intraocular pressure, fixed combination